2000
DOI: 10.1136/vr.146.4.95
|View full text |Cite
|
Sign up to set email alerts
|

Survey of retinal haemorrhages in neonatal thoroughbred foals

Abstract: Twenty-seven of 167 neonatal thoroughbred foals (16 per cent) were found to have retinal haemorrhages after a careful examination of the entire fundus. Experience in differentiating haemorrhages from other lesions, and the selection of foals from normal populations, were considered to have an important effect on their apparent incidence. Bilateral haemorrhages were more common and there was a significantly higher incidence in female foals. The numbers of haemorrhages ranged between one and 20; 36 per cent of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
2
12
2
Order By: Relevance
“…The percentage of foals with retinal hemorrhages (11.4%) in the present study was lower than that previously reported (16%) in healthy Thoroughbred foals in New Zealand 19 ; however, the 95% confidence intervals for the 2 populations overlap, which suggests the prevalence may not be different between these groups. Retinal hemorrhages were previously thought to be associated with NMS, but more recent investigation indicated that this is more common in larger foals and foals born to dams experiencing dystocia, and is not associated with the development of NMS.…”
Section: Discussioncontrasting
confidence: 91%
“…The percentage of foals with retinal hemorrhages (11.4%) in the present study was lower than that previously reported (16%) in healthy Thoroughbred foals in New Zealand 19 ; however, the 95% confidence intervals for the 2 populations overlap, which suggests the prevalence may not be different between these groups. Retinal hemorrhages were previously thought to be associated with NMS, but more recent investigation indicated that this is more common in larger foals and foals born to dams experiencing dystocia, and is not associated with the development of NMS.…”
Section: Discussioncontrasting
confidence: 91%
“…Results of this study are in general agreement with previous ocular descriptions of the newborn foal at later periods of their neonatal age (Barnett 1975; Latimer et al . 1983; Enzerink 1998; Munroe 1995, 1999, 2000a,b; Turner 2004). However, in this study, new information on the ocular characteristics of early newborn foals is added comparing their ocular findings with those observed in foals at later ages.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal haemorrhages in foals have been frequently related to hypoxic‐ischaemic encephalopathy but have been commonly found in otherwise perfectly normal foals, suggesting that they may be of no clinical significance (Munroe and Barnett 1984; Munroe 2000b). Although the aetiology of retinal haemorrhages has not been clarified, different authors consider that they are due to trauma of birth (Johnson and Rossdale 1975; Bistner 1984; Whitley 1990; Munroe 2000b). It has been demonstrated that foals weighing more than 51 kg are at increased risk of having retinal haemorrhages (Munroe 2000b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-and subretinal haemorrages occur in both normal neonatal foals and foals affected with perinatal asphyxia syndrome. They resolve over several days and are of no functional significance (Munroe 2000b).…”
Section: Papillary and Circumpapillary Haze/bleedingmentioning
confidence: 99%